Dzieje parafi i w Odrowążu Podhalańskim w świetle kroniki parafialnej (1844) - Łukaszewska-Haberkowa, Justyna (Archiwa, Biblioteki i Muzea Kościelne, 2011)
The reader is presented with an article based on the chronicle of the parish in Odrowąż, which originated in 1819 and describes its history till the end of the 19th century. The author of the text was Jan Kanty Miś - the first official rector of this parish. He shortly described its history as well as that of the church. He also listed the furnishings of the temple and characterized its mural paintings. The text, written in Latin, also contains biographies of the first two rectors of the parish. At the turn of the nineteenth century many churches affiliated to existing parishes in the southern part of Poland became independent. The first community to have undergone this process was that of Chochołów and later on similar efforts were made by inhabitants of Pieniążkowice. In 1818 the construction of the church started. According to regulations, each new parish should consist of at least one thousand worshippers. At the same time villagers from Odrowąż, which was only 1.5 km away from Pianiążkowice, also commenced the construction of their own temple. In 1819 the decision was made by the authorities to found the new parish in Odrowąż with the villages of Dział, Pieniążkowice and Załuczne becoming its part. In the next years the two constructions were carried on simulataneously, namely the legal one in Odrowąż and the illegal one in Pieniążkowice. The argument between the two communities continued despite intervention of state authorities, the owners of the villages as well as the rector.